Versatile Electrochemical Synthesis of Selenylbenzo[b]Furan Derivatives Through the Cyclization of 2-Alkynylphenols - Doerner, Carlos V.; Scheide, Marcos R.; Nicoleti, Celso R.; Durigon, Daniele C.; Idiarte, Vinícius D.; Sousa, Martinho J. A.; Mendes, Samuel R.; Saba, Sumbal; Neto, José S. S.; Martins, Guilherme M.; Rafique, Jamal; Braga, Antonio L. (Frontiers in Chemistry, 2022)
Herein, we report an electrochemical oxidative intramolecular cyclization reaction between 2-alkynylphenol derivatives with different diselenides species to generate a wide variety of substituted-benzo[b]furans. Driven by the galvanostatic electrolysis assembled in an undivided cell, it provided efficient transformation into oxidant-, base-, and metal-free conditions, in an open system at room temperature. With satisfactory functional group compatibility, the products were obtained in good to excellent yields.